Mechanisms in Neisseria meningitidis for resistance against complement-mediated killing. - Kugelberg, E; Gollan, B; Tang, C (2008)
Bacterial meningitis and septicaemia is a global health problem often caused by Neisseria meningitidis. The complement system is the most important aspect of host defence against this pathogen, and the critical interaction between the two is influenced by genetic polymorphisms on both the bacterial and the host side; variations of the meningococcus may lead to increased survival in human sera, whereas humans with complement deficiencies are more susceptible to meningococcal infections. Here we discuss the mechanisms of meningococcal resistance against complement-mediated killing and the influence of both bacterial and host genetic factors.